2013
DOI: 10.4161/cbt.22621
|View full text |Cite
|
Sign up to set email alerts
|

Divergent control of Cav-1 expression in non-cancerous Li-Fraumeni syndrome and human cancer cell lines

Abstract: Li-Fraumeni syndrome (LFS) is primarily characterized by development of tumors exhibiting germ-line mutations in the p53 gene. Cell lines developed from patients of a LFS family have decreased p53 activity as evidenced by the absence of apoptosis upon etoposide treatment. To test our hypothesis that changes in gene expression beyond p53 per se are contributing to the development of tumors, we compared gene expression in non-cancerous skin fibroblasts of LFS-affected (p53 heterozygous) vs. non-affected (p53 wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…[31] Recent studies have also shown that CAV1 depletion is strictly TP53 dependent through the AMP-activated protein kinase (AMPK)-TP53/p53 signaling. [32,33] The evidence confirmed the existence of the miR222-CAV1-TP53 regulation which was predicted in the network. Therefore, the regulatory relation between CAV1 and the linked miRNAs such as miR-101 and miR-128 in the network, as well as the linked TFs of E2F4 and SP1, might exist in the aggressive breast cancer cell.…”
Section: Discussionsupporting
confidence: 79%
“…[31] Recent studies have also shown that CAV1 depletion is strictly TP53 dependent through the AMP-activated protein kinase (AMPK)-TP53/p53 signaling. [32,33] The evidence confirmed the existence of the miR222-CAV1-TP53 regulation which was predicted in the network. Therefore, the regulatory relation between CAV1 and the linked miRNAs such as miR-101 and miR-128 in the network, as well as the linked TFs of E2F4 and SP1, might exist in the aggressive breast cancer cell.…”
Section: Discussionsupporting
confidence: 79%
“…As an example, HRAS or ABL1-induced oncogenic transformation of mouse fibroblasts caused the transcriptional downregulation of cav-1 (37, 38). In another work, mutations in TP53 gene, encoding p53, resulted in a reduced expression of cav-1 (39). Studies in prostate cancer cells have shown that cav-1 expression can be induced by protein kinase C ε (PKC ε ) through the sequential activation of mitogen-activated protein kinases (MAPK), c-Myc, and androgen receptor (40).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, CAV1 and p53 are co-regulated by a feedforward loop. Reduced CAV1 expression is observed in cells from individuals with Li-Fraumeni syndrome, which is caused by mutations in TP53 (which encodes p53) 101 . Conversely, CAV1 induces p53 activation 97 .…”
Section: Cd36mentioning
confidence: 99%